2019
DOI: 10.1007/s00408-018-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Exhaled Nitric Oxide Measurements and Screening of Obstructive Sleep Apnea in a Sleep-Laboratory Setting: A Cross-Sectional Study

Abstract: Purpose Obstructive sleep apnea (OSA) is a common condition characterized by repetitive collapse of the upper airways and intermittent oxygen desaturation, which may lead to airway inflammation. Here, we explored whether fractional exhaled nitric oxide (FeNO) levels provide a non-invasive screening tool of OSA. Methods Over a 3-month period, FeNO levels were measured in consecutive non-smoking patients referred for a sleep laboratory. All patients underwent full polysomnography. OSA severity was classified bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(55 reference statements)
0
9
1
Order By: Relevance
“…Methodological discrepancies have been claimed as the reason, which is why these studies cannot be easily compared [32]. A mild increase in FeNO was reported in children with OSA [33][34][35], whereas in our study we found no difference in FeNO between children with higher ODI, those with mild (ODI ≥ 1-3 events/h) and moderate-severe (ODI > 3 events/h) and the controls. Summarizing, OSA alone was not the cause of increased FeNO levels.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Methodological discrepancies have been claimed as the reason, which is why these studies cannot be easily compared [32]. A mild increase in FeNO was reported in children with OSA [33][34][35], whereas in our study we found no difference in FeNO between children with higher ODI, those with mild (ODI ≥ 1-3 events/h) and moderate-severe (ODI > 3 events/h) and the controls. Summarizing, OSA alone was not the cause of increased FeNO levels.…”
Section: Discussioncontrasting
confidence: 89%
“…Children with OSA are noted to have increased pro-inflammatory cytokine levels [30,31]. Studies involving children with OSA in which FeNO was measured as an inflammatory parameter have produced contradictory results [32][33][34][35]. Methodological discrepancies have been claimed as the reason, which is why these studies cannot be easily compared [32].…”
Section: Discussionmentioning
confidence: 99%
“…The study of FeNO in the diagnosis of OSAS has led to contradictory findings. Indeed, while some studies described a raising of FeNO level in OSAS [20,21,22,23,24,25], the majority did not confirm the finding [26,27,28,29,30] or just showed a higher concentration in OSAS patients when compared with non-obese healthy controls [31,32,33]. Besides, even considering only those studies with a positive finding, the FeNO level, albeit statistically higher than healthy controls, did not reach a clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, OSA is probably the essential attribution of airway inflammation. Although the analysis of exhaled NO is a non-invasive, harmless, and still not fully standardized method to investigate the pathophysiology of OSA, 13,[31][32][33] based on our findings, CANO could be used as marker of endothelial dysfunction for differentiating patients from healthy subjects. However, the contradictions with the CANO value measured using the simple linear model should be considered the limitation of this technique.…”
Section: Discussionmentioning
confidence: 81%